An Impact of Employee Satisfaction on Customer Satisfaction in Service Sector of Pakistan - Daniel, Adeel; Ashar, Muhammad; Ihsan-Ur-Rehman, Hafiz; Shahbaz, Wahab (Journal of Asian Scientific Research, 2012)
This research paper is intended to establish the impact of the employee satisfaction on the customer satisfaction. Customer satisfaction is the emerging issue nowadays and the present study was conducted to evaluate the customer satisfaction via employee satisfaction. This study is focused on the services sector especially in banking sectors of Pakistan. A stratified random sampling was taken to conduct the field survey. Furthermore, two different questionnaires have been developed on 5 point likert scale to check the responses of employees and customers separately. Further, the five variables have discussed both on the customer side and the employee side: Good care, IT facility, e- message reply, Manager Relationship and Welcome in need of help. It was found that Customer satisfaction is followed by the employee satisfaction.